Syariat Islam Tentang Relasi dan Toleransi Antar Umat Beragama Dalam Alquran - Y Yusefri (Institut Agama Islam Negeri Curup, 2017)
This paper essentially conducted a study on how the provisions of Islamic law that governs the relationship between a Muslim with non-Muslims in order to realize inter-religious harmony. The study was conducted because, since the classical times, there were books of fiqh, which is a collection of the scholar’s ideas about the formulation of Islamic sharia (law) extracted from the source, had not seen yet containing the discussion about many provisions related to the deed of a Muslim with non-Muslims. The object of study is more focused on the verses of Al-Quran related to this issue. By using the analytical approach of interpretation, proved that Islamic law has laid clear provisions regulating the relationship between a Muslim and non-Muslims, including compelled to behave tolerantly, should not enforcing and anarchists.